2020
DOI: 10.1016/j.remn.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico de neumonía COVID-19 en pacientes asintomáticos tras la realización de un PET/TC oncológico

Abstract: Introducción: El 30 de enero de 2020 la organización mundial de la salud (OMS) declaró una emergencia internacional por la pandemia causada por un nuevo coronavirus. Existen algunas indicaciones oncológicas que tienen especial prioridad y se siguen realizando estudios a pesar de la situación actual. En estos estudios hemos encontrado hallazgos sospechosos de neumonía COVID-19 en pacientes asintomáticos. El objetivo de este trabajo es valorar la incidencia de estos hallazgos, describir sus características y val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…From the comprehensive computer literature search of PubMed/MEDLINE and Cochrane databases, 169 records were screened. In total, 11 studies were selected and retrieved in full-text version according to the predefined inclusion criteria [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Conversely, 158 records were excluded because case reports or small case series ( n = 51), reviews, editorials, letters ( n = 39) or because they were outside the field of interest of this review ( n = 68).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the comprehensive computer literature search of PubMed/MEDLINE and Cochrane databases, 169 records were screened. In total, 11 studies were selected and retrieved in full-text version according to the predefined inclusion criteria [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Conversely, 158 records were excluded because case reports or small case series ( n = 51), reviews, editorials, letters ( n = 39) or because they were outside the field of interest of this review ( n = 68).…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies, 2-[ 18 F]FDG PET/CT was performed in patients evaluated for standard indications (mostly oncological indications) and incidental findings suspicious of SARS-CoV-2 infection or COVID-19 at whole-body 2-[ 18 F]FDG PET/CT were described [ 7 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 ]. Only in one study 2-[ 18 F]FDG PET/CT was performed in COVID-19 patients to assess the inflammatory status at the presumed peak of the inflammatory phase [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive confirmatory test observed in 14/23 patients represent a true prevalence of COVID-19 pneumonia of 1.3% in our sample. The prevalence reported by small case series are broadly variable (from 8 to 38%), since they are related with cancer subjects with suspicious CT findings and partial or total absence of laboratory confirmation [22][23][24]. Our very low prevalence could be related with more restrictive criteria applied to select the cancer patients derived to 18 F-FDG PET-CT and the heterogeneous, unpredictable prevalence of the disease during different study periods.…”
Section: Frequency Of Covid-19 Pneumonia In Asymptomatic Cancer Patientsmentioning
confidence: 77%
“…Five of this 6 patients exhibited small lymph nodes (< 1 cm). The results obtained by previous case series applying 18 F-FDG PET-CT were heterogeneous; Albano et al found mediastinal adenopathies in 1/5 confirmed patients [23], and Rasilla et al did not report lymphoid FDG uptake [24].…”
Section: Ct Findings and Fdg Uptake In The Thoraxmentioning
confidence: 91%